Social and Cultural Integration and Adaptation of Migrant Children into Norwegian Society in 1990s and 2000s - S. Yu. Boldyreva; N. E. Pukhovskaya; V. K. Khoruzhenko (Научный диалог)
The authors consider the processes of social and cultural adaptation of migrant children and their integration into the host society in the context of Norway’s immigration policy in the article. Particular attention is paid to the specifics of the country’s immigration policy, strategies for working with immigrant children in the host society, as well as the social consequences of these strategies for Norwegian society. It is emphasized that immigrants and the native population of the country exert mutual influence on each other. Establishment of effective social interactions between them, assimilation of elements of new culture by immigrants has a favorable effect on the internal political stability of the state. It is noted that this is especially important for Norway, which adheres to the policy of multiculturalism. It is concluded that the integration of immigrants into the host community does not happen automatically. The authors also highlight the strengths and weaknesses of the Norwegian immigration policy in relation to children, which to a certain extent calls into question its effectiveness in the long term.